MAPPING THE INTELLECTUAL LANDSCAPE OF HALAL TOURISM RESEARCH: A BIBLIOMETRIC ANALYSIS - Noriza Mohd Saad; Fatihah Norazami Abdullah; Nur Aufa Muhammad Raziff (International Journal of Accounting, Finance and Business, 2023)
This paper aims to conduct a bibliometric study on Halal Tourism. The study analyses sources of publication, authorship, citations, and other bibliometric indicators to identify the research agenda for future studies related to halal tourism. The data for the study was collected using an automated process from Harzing, VOS, Microsoft Excel, and Open Refine databases, covering 343 articles published from 1997 to 2022, and then analyzed using data mining, bibliometric indicators analysis, cluster analysis, network analysis, and word cloud techniques. The study focused on articles related to halal tourism. The study findings identified 160 authors from 53 countries. The paper unveils relevant articles, authors, and journals that have discussed halal tourism. Additionally, the research reveals the geographical locations of influential articles and authors and lists frequently used words that help develop a research agenda highlighting relevant themes, methods, and industries. The study's practical implications help practitioners become aware of the state of the art and the specificities of the most prolific studies. Furthermore, the paper intends to clarify the project themes and tools most used in these works. The study's originality lies in its extensive data analysis and the development of a research agenda, which provides insights into halal tourism research. This study can provide a starting point for future researchers interested in exploring the intellectual landscape of halal tourism research.